CHARACTERISTICS OF INSTRUMENTAL PERFORMANCE - Nosirov Dilmurod Tursinovich (Journals Park Publishing, 2024)
Instrumental performance is a multifaceted art form that encompasses technical mastery, expressive interpretation, and creative innovation. This research paper explores the unique characteristics of instrumental performance, examining aspects such as technique, musicality, interpretation, and stage presence. Following the IMRAD framework, this study examines the factors that contribute to excellent instrumental performances and their impact on audience participation and artistic expression.
Keywords: Instrumental performance, technical mastery, Artistic interpretation, Stage presence, Audience participation.